2008
DOI: 10.5144/0256-4947.2008.102
|View full text |Cite
|
Sign up to set email alerts
|

Increased bone mineral density in postmenopausal women with type 2 diabetes mellitus

Abstract: BACKGROUND AND OBJECTIVESStudies of bone mineral density (BMD) in women with type 2 diabetes mellitus have shown conflicting results. We conducted this study to determine whether postmenopausal women with diabetes have higher BMD than non-diabetic women of similar age, and to investigate the relationship between BMD and relevant clinical characteristics in these groups of women.PATIENTS AND METHODSWe retrospectively analyzed lumbar spine, femoral neck, and radius BMD data and other relevant clinical data for 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 14 publications
2
11
1
Order By: Relevance
“…Eleven of the included studies used DXA to determine aBMD (T2DM n ¼ 4813, control n ¼ 12693) [23][24][25][26][27][28][29][30][31][32][33] at either the total hip or the femoral neck site. Of these DXA studies, seven controlled for age 23,27,[29][30][31][32][33] and four for BMI.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eleven of the included studies used DXA to determine aBMD (T2DM n ¼ 4813, control n ¼ 12693) [23][24][25][26][27][28][29][30][31][32][33] at either the total hip or the femoral neck site. Of these DXA studies, seven controlled for age 23,27,[29][30][31][32][33] and four for BMI.…”
Section: Resultsmentioning
confidence: 99%
“…23,29,30,32 Women with T2DM had a significantly higher aBMD at the total hip in five studies, 25,29,[31][32][33] of which two controlled for age 31,33 and two controlled for both age and BMI; 23,29 two studies showed no significant difference, 23,27 both of which controlled for age and one of which also controlled for BMI. 23 Femoral neck aBMD was significantly higher for older women with T2DM in four studies, 24,26,29,32 two of which controlled for both age and BMI. 29,32 Femoral neck aBMD did not show a significant difference in three studies, 23,27,28 of which two controlled for age 27,28 and one controlled for both age and BMI.…”
Section: Resultsmentioning
confidence: 99%
“…In some studies, patients with T2DM showed no significant difference either in BMD or prevalence of osteoporosis from nondiabetic patients, 1,2 while others have demonstrated either higher BMD in patients with T2DM compared to nondiabetics. 3,4 Recently, there have been reports of adverse impact of antihyperglycaemic medications on BMD in T2DM patients 5,6 and increase risk of fractures with glitazones and protective effect from metformin. 6,7 However, there are limited data that address the impact of various drugs on BMD in diabetic patients.…”
Section: Introductionmentioning
confidence: 99%
“…A similar phenomenon is also observed in humans. Postmenopausal women with type 2 diabetes had higher lumbar spine BMDs than nondiabetic postmenopausal women [3]. Therefore, it is considered that the SDTfa/fa rat may be a good model for bone abnormalities in postmenopausal women with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Bone mineral density (BMD) is a good predictor of bone strength because fracture risk increases with a decrease in BMD [1,14]. BMD is decreased in patients with type 1 diabetes [15] but is decreased [17], normal [15] or increased [3] in patients with type 2 diabetes. Unlike patients with type 1 diabetes, the relationship between BMD and fracture risk in patients with type 2 diabetes remains controversial.…”
mentioning
confidence: 99%